Efeitos de um programa de cinesioterapia por meio de interação virtual em mulheres idosas - Ponte, Joceléia Müller (2013)
The objectives of this study were to evaluate the effects of a program cinesiotherapy through virtual interaction using the Xbox 360 with Kinect in functional fitness, and assess whether the program provides an increase in muscle strength of upper and lower limbs in a group elderly women in comparison with a group that performed traditional physical activities. The study is a quantitative, experimental character, with delineation of pre-and post-tests with the use of eight weeks. The sample was composed of 16 active elderly women, aged between 60 and 80 years. The scientific production I present the results of the physical fitness test for the elderly. The results of upper limb strength in the experimental group showed a significant difference (p = 0.020), whereas the agility and balance significantly different for both groups (p = 0.027), aerobic endurance showed differences only in the control group (p = 0.042). The scientific production II present the results of the performance evaluation of the extensor and flexor muscles of the knee and shoulder. Were observed in the group of videogame significant differences in peak torque of the extension movement of the right leg at angular velocities of 60°/s and 180º/s (p = 0.043), and the peak ring flexion of the left arm at the speed angle of 60°/s (p = 0.043). The results presented in these productions suggest effects on functional fitness and muscle strength of upper and lower limbs through physical activities with the use of video games. Exercise programs traditional or performed in virtual form can minimize or even prevent functional decline, and is an effective alternative intervention for physical activities with elderly people.